UK B.1.1.7 (Alpha) variant exhibits increased respiratory replication and shedding in nonhuman primates - Kyle Rosenke; Friederike Feldmann; Atsushi Okumura; Frederick Hansen; Tsing-Lee Tang-Huau; Kimberly Meade-White; Benjamin Kaza; Julie Callison; Matthew C. Lewis; Brian J. Smith; Patrick W. Hanley; Jamie Lovaglio; et al. (Emerging Microbes and Infections, 2021)
The continuing emergence of SARS-CoV-2 variants calls for regular assessment to identify differences in viral replication, shedding and associated disease. In this study, we compared African green monkeys infected intranasally with either the UK B.1.1.7 (Alpha) variant or its contemporary D614G progenitor. Both variants caused mild respiratory disease with no significant differences in clinical presentation. Significantly higher levels of viral RNA and infectious virus were found in upper and lower respiratory tract samples and tissues from B.1.1.7 infected animals. Interestingly, D614G infected animals showed significantly higher levels of viral RNA and infectious virus in rectal swabs and gastrointestinal tissues. Our results indicate that B.1.1.7 infection in African green monkeys is associated with increased respiratory replication and shedding but no disease enhancement similar to human B.1.1.7 cases.